Mas-related G protein-coupled receptor MRGPRX2 in human basophils: Expression and functional studies - Toscano, Alessandro; Elst, Jessy; Van Gasse, Athina L.; Beyens, Michiel; van der Poorten, Marie-Line; Bridts, Chris H.; Mertens, Christel; Van Houdt, Michel; Hagendorens, Margo M.; Van Remoortel, Samuel; Timmermans, Jean-Pierre; Ebo, Didier G.; et al. (Frontiers in Immunology, 2023)
Background Occupancy of MRGPRX2 heralds a new era in our understandings of immediate drug hypersensitivity reactions (IDHRs), but a constitutive expression of this receptor by basophils is debated. Objective To explore the expression and functionality of MRGPRX2 in and on basophils. Methods Basophils from patients with birch pollen allergy, IDHRs to moxifloxacin, and healthy controls were studied in different conditions, that is, in rest, after stimulation with anti-IgE, recombinant major birch pollen allergen (rBet v 1), moxifloxacin, fMLP, substance P (SP), or other potential basophil secretagogues. In a separate set of experiments, basophils were studied after purification and resuspension in different media. Results Resting whole blood basophils barely express MRGPRX2 on their surface and are unresponsive to SP or moxifloxacin. However, surface MRGPRX2 is quickly upregulated upon incubation with anti-IgE or fMLP. Pre-stimulation with anti-IgE can induce a synergic effect on basophil degranulation in IgE-responsive subjects after incubation with SP or moxifloxacin, provided that basophils have been obtained from patients who experienced an IDHR to moxifloxacin. Cell purification can trigger a “spontaneous” and functional upregulation of MRGPRX2 on basophils, not seen in whole blood cells, and its surface density can be influenced by distinct culture media. Conclusion Basophils barely express MRGPRX2 in resting conditions. However, the receptor can be quickly upregulated after stimulation with anti-IgE, fMLP, or after purification, making cells responsive to MRGPRX2 occupation. We anticipate that such “conditioned” basophils constitute a model to explore MRGPRX2 agonism or antagonism, including IDHRs originating from the occupation of this receptor.